Distinguishing truly recalcitrant prurigo nodularis from poor treatment adherence: a response to treatment-resistant prurigo nodularis [Response to letter] - Kowalski EH; Kneiber D; Valdebran M; Patel U; Amber KT (Dove Medical Press, 2019)
Eric H Kowalski,1 Diana Kneiber,1 Manuel Valdebran,2 Umangi Patel,1 Kyle T Amber11Department of Dermatology, University of Illinois at Chicago, Chicago, IL, USA; 2Department of Dermatology, University of California-Irvine, Irvine, CA, USAKolli et al shed light on a pertinent issue of poor adherence to therapy in the treatment of prurigo nodularis (PN).1 While our intention was to cover recalcitrance in the sense of medical failure, Kolli et al bring up an extremely valuable point: adherence to therapy is dismal.2 Escalation of therapy as a result of poor compliance may result in unintended adverse effects from the more potent systemic therapies delineated in the treatment of PN. Thus, ensuring compliance with the treatment protocol should be a priority.In our view, PN is most often a phenotypic manifestation of chronic pruritus secondary to a host of diseases. Presumably, the relative adherence to treatment for the underlying cause of the PN, in cases where there is one, has a large role to play in the recalcitrance of the PN. This is perhaps most glaring in the case of atopic dermatitis (AD). AD has been identiﬁed to contribute to PN development in nearly 50% of PN patients.3 Assessment of nonadherence, as well as steroid phobia has been well documented in the AD population and almost certainly contributes to the development of clinically deemed recalcitrant PN in this population.4,5 Because of the well-established efﬁcacy of topical corticosteroids in the treatment of atopic dermatitis, it is likely that atopic PN would prove more responsive. Thus, “treatment resistant” atopic PN, requires serious con- sideration of nonadherence. Clinical data on nonadherence in nonatopic PN patients, however, remains undetermined.Regardless of the primary underlying cause, patients receiving supervised phototherapy in the outpatient setting offer insight into truly recalcitrant PN due to complete adherence. A recent review on phototherapy in treatment of PN showed that in 5 out of 11 studies, patients experienced recalcitrant disease.6 Thus, even in a supervised setting where adherence could be monitored, numerous cases were recalcitrant.Innovation in adherence strategies across a wide spectrum of therapies ideally will result in fewer “treatment-resistant” cases.7–9 We agree with Kolli et al, that it remains vital to distinguish between poor adherence and medical failure.This is in response to the Letter to the Editor